Copper sulfide nanoparticles as high-performance cathode materials for magnesium secondary batteries. Issue 26 (22nd June 2018) - Wu, Mengyi; Zhang, Yujie; Li, Ting; Chen, Zhongxue; Cao, Shun-an; Xu, Fei
Abstract : Copper sulfide nanoparticles are used as low-cost and high-performance cathode materials for magnesium secondary batteries. Abstract : Magnesium secondary batteries are promising candidates for large-scale energy storage systems with high safety, because of the dendrite-free electrodeposition of the magnesium anode. However, the search for available cathode materials remains a significant challenge, hindering their development. In this work, we report copper sulfide nanoparticles as high-performance cathode materials for magnesium secondary batteries, which deliver a high reversible capacity of 175 mA h g −1 at 50 mA g −1 . The cathode also shows an excellent rate capability providing 90 mA h g −1 at 1000 mA g −1 and an outstanding long-term cyclability over 350 cycles. The beneficial properties are ascribed to the small-sized copper sulfide particles which facilitate the solid-state diffusion kinetics. Further investigation on the mechanism demonstrates that the reaction is a typical conversion reaction, and the excellent cycling stability is due to the CuS nanoparticles which are not facile to aggregate during cycling. This work introduces an abundant, low-cost and high-performance cathode material for magnesium secondary batteries, and provides feasibility for the practical application of magnesium secondary battery systems in large-scale energy storage devices.